Live-cell imaging of photosystem II antenna dissociation during state transitions - Iwai, Masakazu (National Academy of Sciences, 2009)
Plants and green algae maintain efficient photosynthesis under changing light environments by adjusting their light-harvesting capacity. It has been suggested that energy redistribution is brought about by shuttling the light-harvesting antenna complex II (LHCII) between photosystem II (PSII) and photosystem I (PSI) (state transitions), but such molecular remodeling has never been demonstrated in vivo. Here, using chlorophyll fluorescence lifetime imaging microscopy, we visualized phospho-LHCII dissociation from PSII in live cells of the green alga Chlamydomonas reinhardtii. Induction of energy redistribution in wild-type cells led to an increase in, and spreading of, a 250-ps lifetime chlorophyll fluorescence component, which was not observed in the stt7 mutant incapable of state transitions. The 250-ps component was also the dominant component in a mutant containing the light-harvesting antenna complexes but no photosystems. The appearance of the 250-ps component was accompanied by activation of LHCII phosphorylation, supporting the visualization of phospho-LHCII dissociation. Possible implications of the unbound phospho-LHCII on energy dissipation are discussed.